2021
DOI: 10.2147/cmar.s328279
|View full text |Cite
|
Sign up to set email alerts
|

HPV Genotype Specific and Age Stratified Immediate Prevalence of Cervical Precancers and Cancers in Women with NILM/hrHPV+: A Single Center Retrospective Study of 26,228 Cases

Abstract: To investigate the prevalence of precancers [high-grade squamous intraepithelial lesion (HSIL) and adenocarcinoma in situ (AIS)] and cancers [squamous cell carcinoma (SCC) and adenocarcinoma (ADC)] in various high-risk human papillomavirus (hrHPV) genotypes or age groups among women with negative for intraepithelial lesion or malignancy (NILM) and hrHPV-positive pap results. Materials and Methods: In total, 26,228 women with NILM/hrHPV+ were included in the study. Among them, 5893 had immediate follow-up biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…Our previous study in NILM/hrHPV+ women demonstrated lower risk of cervical precancer but higher risk of cancer in the older patient group 30. In the current study, the prevalence of HSIL+squamous lesions or AIS+ glandular lesions showed no significant difference among different age groups.…”
Section: Discussioncontrasting
confidence: 61%
“…Our previous study in NILM/hrHPV+ women demonstrated lower risk of cervical precancer but higher risk of cancer in the older patient group 30. In the current study, the prevalence of HSIL+squamous lesions or AIS+ glandular lesions showed no significant difference among different age groups.…”
Section: Discussioncontrasting
confidence: 61%
“…Our previous study showed that in the NILM/hrHPV-positive population, the older patient group exhibited a lower risk of cervical precancer but a higher risk of cancer. 21 Similarly, in ASC-US/hrHPV-positive women, the prevalence of cervical SCC is significantly higher in older women than in younger women. 22 In the current study, 25-39 age years group showed a significantly higher prevalence of CIN1 ( p = .032).…”
Section: Discussionmentioning
confidence: 97%
“…Recognizing that women who are NILM but have non-16/18 HR-HPV persistence are still at risk for precancerous lesions; however, the utility of the current strategy is confined to a higher risk in women who have type-specific persistence of non-16/18 genotypes. This is especially true for younger NILM women, who had a significantly higher HSIL prevalence than older women (27). When no precursor lesion is detected at the initial screening, there is no agreement on the duration of follow-up on non-HPV16/18 persistence before referral to colposcopy or treatment.…”
Section: Limitations On Current Managementmentioning
confidence: 99%
“…Moreover, the prevalence and risk for HSIL decline with increasing age in women who are NILM (1,36). However, when an age cutoff of 40 years was used, the prevalence of HSIL in younger women who were NILM was significantly higher than that in older women, and the group of older women conferred a lower risk for cervical precursor lesions and a higher risk for cancer compared to the group of younger women (27).…”
Section: Risk For Progression To Cervical Preneoplastic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation